METHODS OF HIDING DATA IN COMPUTER NETWORKS: FROM CLASSICS TO IoT AND Ai (Computer systems and information technologies, 2025)
The article presents an overview of key methods in network steganography, including the classification of data hiding techniques in network protocols and discussion of promising directions for further research. Special attention is paid to the use of steganography in modern network environments such as IoT, as well as the application of artificial intelligence to traffic masking. The paper also outlines current approaches to hidden channel detection and threat modeling in digital communication systems.
Keywords: network steganography; covert channels; IoT; transmission protocols; cybersecurity; steganalysis; information security